2001
DOI: 10.1074/jbc.m008150200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Inhibition by ω-3 Fatty Acids

Abstract: Recent data suggest that -3 fatty acids may be effective in epilepsy, cardiovascular disorders, arthritis, and as mood stabilizers for bipolar disorder; however, the mechanism of action of these compounds is unknown. Based on earlier studies implicating -3 fatty acids as inhibitors of protein kinase C activity in intact cells, we hypothesized that -3 fatty acids may act through direct inhibition of second messenger-regulated kinases and sought to determine whether the -3 double bond might uniquely confer pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 36 publications
(23 reference statements)
6
85
1
3
Order By: Relevance
“…DHA increases PKC activity in macrophage cell lines, 65 but inhibits activity of isolated catalytic PKC subunits. 66 In the present study, there was no significant difference in total PKC activity, but an effect on PKC isoforms cannot be ruled out.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…DHA increases PKC activity in macrophage cell lines, 65 but inhibits activity of isolated catalytic PKC subunits. 66 In the present study, there was no significant difference in total PKC activity, but an effect on PKC isoforms cannot be ruled out.…”
Section: Discussioncontrasting
confidence: 58%
“…Exogenous DHA decreases cytosolic and particulate PKA activity in macrophage tumor cells (AK-5) 65 and decreases catalytic PKA activity in vitro. 66 In the current study, n-3 PUFA deprivation significantly increased basal PKA activity in the frontal cortex due to a loss of the inhibitory effect of DHA possibly. We also observed that the addition of DHA to rat primary cortical astrocytes decreased PKA activity.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, n-3 PUFA intake blocks the activity of mitogen-activated protein kinase, 25) which is involved in the modulation of central sensitization induced by inflammatory and neuropathic pain, suggesting another potential pathway to inhibit pain transmission. 26,27) Interestingly, intake of a-linolenic acid, one of the n-3 PUFAs, has been reported to suppress the production of lysophosphatidic acid, a factor strongly related to the development of neuropathic pain. 28) Docosahexaenoic acid (DHA), one of the n-3 PUFAs, has a 22-carbon chain with six double bonds.…”
Section: N-3 Pufas and Painmentioning
confidence: 99%
“…Oleic acid appears to affect indirectly TAM's dissociation from cellular antiestrogen binding sites (Hwang, 1987), an effect that could increase the intracellular concentrations of free drug. Since n-3 PUFAs have many biological activities, they may play a role in modifying TAM's actions, including an ability to inhibit protein kinases (Mirnikjoo et al, 2001). g-linolenic acid has several properties that might make it antitumorigenic.…”
Section: Soy Dietary Fat Vegetables and Antiestrogen Responsivenessmentioning
confidence: 99%